TINDAK TUTUR ILOKUSI DALAM LIRIK LAGU ALBUM MONOKROM KARYA MUHAMMAD TULUS RUSDY - Giyanti Giyanti; Rizki Joko Nurcahyo; Diah Iskafatmawati Saputri (Universitas Islam Negeri Raden Mas Said Surakarta, 2019)
This study aims to describe the forms of illocutionary speech acts classification in the lyrics of the song Monochrome album by Muhammad Tulus Rusdi. Illocutionary speech acts have a communicative function between the speaker and the interlocutor, so it is through this speech act that it can be known the message contained in the song lyrics delivered by Muhammad sincerely Rusdi to music lovers. The data source in this study is the song lyrics in the Monochrome Album by Muhammad Tulus Rusdy which consists of 10 songs: Strong Man, Farewell, Space Alone, Soul Swap, Infatuation, Light, Sky Gray, Masterpiece, and Hurry. This research uses a theoretical approach, which is a pragmatic approach. The method used in this research is descriptive qualitative. The technique used in this study is refer to and note. The results of the study showed that there were 96 data included in the action of the ilocuis speech. Illocutionary speech acts include (1) assertive speech acts, namely: notifying, stating, complaining, demanding, and suggesting. (2) directive speech acts, namely: asking, pleading, advising, commanding. (3) declarative speech acts, namely: naming. (4) expressive speech acts, namely praising and thanking. (5) commissive speech acts, namely promises.Â Keywords: illocution; song lyrics; monochrome; speech act; sincere